Children born of war in the twentieth century - Lee, Sabine (Manchester University Press, 2017)
This book explores the life courses of children born of war in different twentieth-century conflicts, including the Second World War, the Vietnam War, the Bosnian War, the Rwandan Genocide and the LRA conflict. It investigates both governmental and military policies vis-a-vis children born of war and their mothers, as well as family and local community attitudes, building a complex picture of the multi-layered challenges faced by many children born of war within their post-conflict receptor communities. Based on extensive archival research, the book also uses oral history and participatory research methods which allow the author to add the voices of the children born of war to historical analysis.